How to Cultivate Cyber Security Culture? The Evidences from Literature - Akhyari, Nasir; Syahrul, Fahmy; Wan Roslina, Othman; Noor Suhana, Sulaiman; Nooraida, Samsudin; Azham, Ahmad; M R A, Hamid (University College TATI, 2023)
Cyber Security Culture (CSC) is a culture that could produce a secure cyber space and could improve the quality of cyber world engagement. Despite many benefits that could be offered by CSC, there is a lack of models and guidelines on how to cultivate this culture. This paper discusses the concept of CSC model in terms of elements that form the model to suggest how CSC could be cultivated. Information Security Culture (ISC) model developed by [1] is used as a framework in discussing the concept of CSC. A literature search also is conducted to find and analyses the most suitable elements for CSC. A new model of CSC was proposed as a result of this study. The findings could provide better understanding of CSC and could be used as baseline to conduct more research on CSC.